From Microfascism to Joyful Affects: A Posthuman Approach to Social Media Redesign - IV, J.J. Sylvia (Journal of Posthumanism, 2024)
This paper scrutinizes the micropolitical fascism latent in social media platforms’ algorithmic designs, which, according to Deleuze & Guattari (2009) and Crano (2022), foster desires for uniformity and control that may escalate into authoritarianism, threatening democracy and free speech. It considers the paradoxical nature of social media in enhancing connectivity while potentially inducing loneliness, an emotional state Arendt links to fascism, and their role in amplifying negative emotions, spreading disinformation, and conspiracy theories, such as QAnon. Delving into the mechanics of such designs, the paper leverages a monist informational ontology to dissect subjectivation processes and envisage overcoming these microfascist inclinations. It suggests a radical redesign of social media platforms that eschews analytics-driven narratives in favor of fostering joyful affect and novel subjectivities. This reimagining aims to detach social media storytelling from analytics and data exploitation, promoting a posthuman model for platform design that resists the generation of microfascist desires.